Optimization of Strategic Areas in Regional Economic Recovery: Tourism Perspectives - Sukardi; Durratun Nashihah; Denny Iswanto; Baiq Dewi Kamariani; Firdausi Dhulhijjahyani (International Journal of Sustainable Applied Sciences, 2024)
This research contributes in the form of ideas and modeling of tourism potential development in the region. This research uses Soft System Methodology. This method used 4 stages: The first stage, the problem situation is considered problematic. In the second stage, the problem situation is expressed. The third stage is the root definition of the relevant purposeful activity system. The fourth stage is the conceptual models of the system named in the root definition. Based on the research, it was found that Pangandaran Regency, which is a new autonomous region, has tourism potential that can be developed, especially marine tourism that can support the regional economy. On the other hand, tourism potential is influenced by the geographical condition of Pangandaran Regency which is included in the National Tourism Strategic Area so it is hoped that this program can have a significant impact on regional economic recovery efforts. Based on the Regional Government Plan of Pangandaran 2022, it already has various strategies for tourism development, but it has not been able to run optimally due to the absence of a tourism development model as an economic recovery program.